G63(P) Treatment patterns in spinal muscular atrophy: interviews with healthcare professionals in the United Kingdom. (25th October 2020) - Dabbous, O; Germain, N; Maru, B; Aballéa, S; Desroches, M; Toumi, M; Loukes, J; Arjunji, R
Abstract : Aims: Spinal muscular atrophy (SMA) is a rare genetic disorder characterized by weakness and atrophy in skeletal muscles. Excluding the prenatal onset form (type 0), SMA is classified into 4 phenotypes based on severity, with type 1 being the most severe. The recent advent of the first disease-modifying therapies has dramatically improved the outlook for patients with SMA, but little is known about current treatment patterns. The objective of this study was to collect data on standard of care treatment patterns in SMA types 1, 2, and 3 in the UK prior to the availability of disease-modifying therapies through health care professional (HCP) interviews. Methods: HCPs who had seen at least two patients with SMA in the past 12 months were recruited through contacts in clinical centers in the UK. Informed consent was obtained from all respondents with subsequent telephone interviews. Results: Interviews were conducted with 16 HCPs from eight UK regions: nine neurologists, three pulmonologists, two physiotherapists, one nurse, and one health visitor. Participants reported that paths to diagnosis depend on symptom timing and HCPs involved. Time to diagnosis was estimated at up to 3 months for SMA type 1, and up to 12 months for SMA types 2 and 3. HCPs agreed on key approaches to management and care coordination. Patients' geographic proximity to a hospital often determines who coordinates care. Although the concept of segmenting SMA disease progression into defined, discrete phases was controversial, there was broad concurrence on key parameters of ventilation, nutrition, and mobility. Many HCPs are involved in patient care, with community support being essential; however, HCPs were not able to report on palliative care and personal social services. The challenges faced by HCPs in SMA are numerous and include a lack of resources and a lack of effective treatment options. Conclusion: HCP reports underline the complexity of treatment coordination for SMA between hospitals and communities. Management is focused on ventilation, feeding, and mobility, with the involvement of a large number of HCPs. A comprehensive SMA care model is needed.